Surgical Management of Intraocular Lens Dislocations - Gül, A.; Duran, M.; Can, E.; Yücel, O.E.; Süllü, Y. (Conselho Brasileiro de Oftalmologia abo@cbo.com.br, 2015)
Purpose: To report and compare the surgical, visual, and anatomical outcomes following treatment of dislocated intraocular lenses (IOLs). Methods: The medical records of 28 eyes of 28 patients were evaluated. Age, gender, pre-and postoperative best-corrected visual acuity (BCVA), surgical methods, and complications were recorded. Results: Pre-and postoperative BCVA ranged from counting fingers to 20/32 and from counting fingers to 20/25, respectively. Late-onset dislocations were the most frequently observed complication. The most frequent surgical method was IOL repositioning in 15 of 28 patients, followed by IOL exchange in 11 patients, and IOL removal in 2 patients. Only 1 patient required surgical re-intervention with IOL capture. Conclusions: Visual acuity improved following the use of either IOL repositioning or IOL exchange. No superiority of one method over the other was observed. In the present retrospective case series, management of dislocated IOLs with repositioning or exchange of the primary implant conferred comparable surgical and visual outcomes.
Keywords: Intraocular/Methods; Lens Implantation; Lenses Intraocular; Visual Acuity/Physiology